Protocol for analyses of adverse event data from randomized controlled trials of statin therapy - Mihaylova, B; Reith, C (Elsevier, 2016)
The Cholesterol Treatment Trialists' (CTT) Collaboration was originally established to conduct individual participant data metaanalyses of major vascular events, cause-specific mortality, and site-specific cancers in large, long-term, randomized trials of statin therapy (and other cholesterol-modifying treatments). The results of the trials of statin therapy and their associated metaanalyses have shown that statins significantly reduce the risk of major vascular events without any increase in the risk of nonvascular causes of death or of site-specific cancer, but do produce small increases in the incidence of myopathy, diabetes, and, probably, hemorrhagic stroke. The CTT Collaboration has not previously sought data on other outcomes, and so a comprehensive meta-analysis of all adverse events recorded in each of the eligible trials has not been conducted. This protocol prospectively describes plans to extend the CTT meta-analysis data set so as to provide a more complete understanding of the nature and magnitude of any other effects of statin therapy